Nilai-Nilai Pendidikan Islam Yang Terkandung Pada Pelaksanaan Praktek Puasa Ramadhan - Hanifa Ghina Rihan; Putri Cahyati; Joya Anggelia; Sherin Naura Efendi; Wismanto Wismanto (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Ramadan fasting is an important religious ritual according to Islamic law. Therefore, fasting is one of the five pillars of Islam and is mandatory for all Muslims who are ismuqaraf (mature and sensible) and are unable to practice it. As a religion that is full of educational and teaching values, Islam focuses on improving and developing the self and character of its followers. The religious practices contained therein, whatever their form, are always aimed at educating and advancing the servant. The obligations that Islam imposes on its people always contain wisdom and benefit for its people. Likewise with the command to fast. The aim of this research is to reveal the values of Islamic education contained in the implementation of the practice of fasting during Ramadan. The method used in this research is a qualitative method with a research library approach which uses books, magazines and articles as the main sources. The results of this research show that the value of Islamic education is implied in fasting as an obligation that must be fulfilled once a year, so that every mukhallaf is motivated to carry out his wishes with deep sincerity and great enthusiasm. Rewards, wisdom and happiness from Allah Subhanahu Wata'ala.